Corporate memory records and information management in the knowledge age - Megill, Kenneth A. 1939-; Gale Group (München K.G. Saur, 2005)
"Corporate memory is the body of active and historical information that an organization has that is worth sharing, managing and preserving to enable it to function effectively. This book describes the most up-to-date methods and approaches to this essential function, as well as the adoption of an international standard for record management. Aimed at records managers and archivists responsible for maintaining and managing information within an organization."--GVRL description.
Preface to Second edition -- Introduction -- Chapter 1: Empowerment -- Chapter 2: The memory problem -- Chapter 3: The corporate memory and Records Management -- Chapter 4: The document as a verb -- Chapter 5: Valuing documents -- Chapter 6: The corporate memory manager -- Chapter 7: The technologies -- Chapter 8: Performance Centered Learning -- Chapter 9: Workflow -- Chapter 10: Improvements -- Chapter 11: Making it happen -- For further information -- Appendix: ISO Standard -- Glossary -- Index.
Electronic reproduction.
Keywords: Corporations -- Information services -- Management; Information resources management; Knowledge management; Information retrieval; Records -- Management; Documentation; Electronic books